Nursing care in the prevention of occupational accidents in health services (Research, Society and Development, 2025)
Occupational accidents in healthcare settings remain a global challenge, particularly among nursing professionals, who are at the forefront of patient care and exposed to multiple occupational risks. This study aims to analyze, through a systematic literature review, the main nursing strategies and care practices aimed at preventing occupational accidents in hospital environments, based on evidence published between 2015 and 2025. Searches were conducted in PubMed, SciELO, LILACS, and ScienceDirect databases using DeCS/MeSH descriptors combined with Boolean operators AND and OR. Following the PRISMA 2020 protocol, original studies and systematic reviews addressing educational, ergonomic, or managerial interventions for occupational safety were included. The findings show that continuous educational actions, safety culture, proper use of personal protective equipment (PPE), ergonomics, and effective communication are key pillars in reducing the risk of accidents. It is concluded that strengthening permanent education and organizational safety culture is essential for promoting safer and healthier work environments.